STUDENTS' PERCEPTIONS OF DISTANCE LEARNING FOR MULTIMEDIA AND SOCIAL MEDIA COURSES AT IAIN KEDIRI - Daroini, Ahmad Mamun (Kitaba, 2024)
This research aims to determine the perceptions of 3rd semester PBA students regarding the implementation of distance learning (PJJ) in PBA multimedia and social media courses at the IAIN Kediri postgraduate course. The method used is Percentage Descriptive Analysis. Sampling was carried out using a random sampling technique using the Slovin Formula, with 9 people taken as samples. Perception indicators according to Walqito and Wulandari, namely: absorption of stimulus, understanding or understanding and assessment or evaluation. The results of the analysis show that IAIN Kediri Postgraduate students' perceptions of the implementation of Distance Learning (PJJ) in Multimedia and Social Media PBA courses have been well received.